MicroRNA in modern genetics - Thapa, JB (Journal of Pathology of Nepal, 2012)
In recent years microRNAs have emerged as important players in modern genetics. This review attempts to introduce the biogenesis of microRNA and its important physiological role in protein synthesis. The association of microRNA with different cancers is discussed. Lastly the frontier field of therapy based on microRNAs to treat different diseases is introduced. Journal of Pathology of Nepal (2012) Vol. 2, 313-316 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6886